Refined Sr2FeMoO6 interface realized with photoemission and magnetization analysis - Angervo Ilari; Saloaro Minnamari; Granroth Sari; Huhtinen Hannu; Paturi Petriina (Elsevier B.V., 2022)
We investigate the effects of post-annealing on a set of identically deposited Sr2FeMoO6 (SFMO) thin films. The annealing provides a significant enhancement to ferrimagnetic exchange, evidenced by almost 40 K increase in Curie temperature. The electronic nature of the film surface is our focus of interest. The detailed analysis on oxygen 1s, strontium 3d, molybdenum 3d spectrum along with changes in the carbon contamination show purification from additional phases and significant valence fluctuation. Successful treatment provides films with higher Curie temperature and diminished surface contamination. Annealing therefore provides a possible method of reobtaining a portion of the valuable bulk attributes at interfaces in e.g. spin valve structures.